Non-canonical Roles of Telomerase: Unraveling the Imbroglio - Ségal-Bendirdjian, Evelyne; Geli, Vincent (Frontiers in Cell and Developmental Biology, 2019)
Telomerase plays a critical role in stem cell function and tissue regeneration that depends on its ability to elongate telomeres. For nearly two decades, it turned out that TERT regulates a broad spectrum of functions including signal transduction, gene expression regulation, and protection against oxidative damage that are independent of its telomere elongation activity. These conclusions that were initially obtained mainly in cell lines overexpressing telomerase were further strengthened by in vivo models of ectopic expression of telomerase or in models of G1 TERT knockout mice without detectable telomere dysfunction. However, the latter models were questioned due to the presence of aberrantly shortened telomere in the germline of the parents TERT+/– that were used to create the G1 TERT–/– mice. The physiological relevance of the functions associated to overexpressed telomerase raised also a number of concerns due to artifactual situations and localizations and complications to quantify the level of TERT. Another concern with non-canonical functions of TERT was the difficulty to separate a direct TERT-related function from secondary effects. Despite these concerns, more and more evidence accumulate for non-canonical roles of telomerase that are non-obligatory extra-telomeric. Here, we review these non-canonical roles of the TERT subunit of telomerase. In addition, we emphasize recent results that link TERT to mitochondria and protection to reactive oxygen species suggesting a protective role of TERT in neurons. Throughout this review, we dissect some controversies regarding the non-canonical functions of telomerase and provide some insights to explain these discrepancies. Finally, we discuss the importance of understanding these alternative functions of telomerase for the development of anticancer strategies.